Bone tumor reconstruction with the Ilizarov method. Issue 4 (17th July 2012) - McCoy, Thomas H.; Kim, Han Jo; Cross, Michael B.; Fragomen, Austin T.; Healey, John H.; Athanasian, Edward A.; Rozbruch, S. Robert
Abstract Background and Objectives Patients with musculoskeletal tumors can face large bone deficiency, deformity, and nonunion. Distraction osteogenesis via the Ilizarov method may be useful for reconstruction of these deficiencies allowing limb preservation and optimizing function. Methods We reviewed 20 patients with a range of musculoskeletal tumors necessitating surgical treatment. The group included 9 females and 11 males with a mean age of 22.6 (8–58) years at a mean follow up of 81.7 (26–131) months. The mean bone deficiency was 7.9 (1.2–18.0) cm. Results The mean lengthening achieved was 7.1 (3.5–18.0) cm over an EFI of 33.5 (range, 9.5–58.3) days/cm. This treatment resulted in 10 excellent and 3 good ASAMI bone scores, 10 excellent and 3 good ASAMI function scores, a mean lower extremity MSTS score of 93% and a mean upper extremity MSTS score of 87%. Treatment resulted in 2 complications, 18 obstacles, and 6 problems. Conclusion The Ilizarov method is an effective technique for limb reconstruction of bone tumors, although extended time in external fixation is required. Since no one in this group received simultaneous chemotherapy or radiotherapy, we cannot comment on use of the Ilizarov method with these treatments. Further use and clinical follow‐up is warranted. J. Surg. Oncol. 2013;107:343–352. © 2012 Wiley Periodicals, Inc.